2015
DOI: 10.1007/s40495-015-0018-x
|View full text |Cite
|
Sign up to set email alerts
|

“Curcumin, the King of Spices”: Epigenetic Regulatory Mechanisms in the Prevention of Cancer, Neurological, and Inflammatory Diseases

Abstract: Curcumin (diferuloylmethane), a polyphenolic compound, is a component of Curcuma longa, commonly known as turmeric. It is a well-known anti-inflammatory, anti-oxidative, and anti-lipidemic agent and has recently been shown to modulate several diseases via epigenetic regulation. Many recent studies have demonstrated the role of epigenetic inactivation of pivotal genes that regulate human pathologies, such as neurocognitive disorders, inflammation, obesity, and cancers. Epigenetic changes involve changes in DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(114 citation statements)
references
References 86 publications
2
108
0
4
Order By: Relevance
“…CMN has a number of activities such as antioxidant, antiinflammatory, antiviral, antibacterial, antifungal and anticancer. CMN has potential in number of diseases such as arthritis, Alzheimer's disease, diabetes and allergies [13][14][15][16] . Quercetin (QCN) is a flavonol, which is a subclass of flavonoids.…”
Section: Research Papermentioning
confidence: 99%
“…CMN has a number of activities such as antioxidant, antiinflammatory, antiviral, antibacterial, antifungal and anticancer. CMN has potential in number of diseases such as arthritis, Alzheimer's disease, diabetes and allergies [13][14][15][16] . Quercetin (QCN) is a flavonol, which is a subclass of flavonoids.…”
Section: Research Papermentioning
confidence: 99%
“…curcumin is a natural dietary polyphenol with documented antiinflammatory, antioxidant and antineoplastic properties [16]; it is the most commonly used spice in India and in Ayurveda and traditional chinese medicine [17]. Several papers demonstrated that curcumin affects different steps of cancer progression.…”
Section: Curcuminoidsmentioning
confidence: 99%
“…curcumin has been shown to be a strong suppressor of NF-kB that in turn down regulates the expression levels of NF-κB-regulated gene products; it inhibits the activation of IkB kinase (IKK) and, thus, prevents the phosphorylation of IkB and the subsequent translocation of NF-kB to the nucleus [17]. Curcumin also enhances cell death or apoptosis via inhibition of the MAPKs pathway, which includes c-Jun N-terminal kinases (JNKs) and extracellular signal-regulated kinases (ERKs) [16]. Moreover, Shah and colleagues indicate that Curcumin, as natural source, is able to overcome drug resistance as well as to reduce cytotoxicity profile of the conventional drug in Acute Myeloid Leukemia patients.…”
Section: Curcuminoidsmentioning
confidence: 99%
“…Several studies have shown that Curcumin is eight times more powerful than vitamin E in preventing lipid peroxidation, as marker of oxidative stress (Boyanapalli and Tony Kong, 2015). In addition to its chemotherapeutic activity, Curcumin has also been cited as a potential chemopreventive agent (Hsu and Cheng, 2007).…”
Section: Standard Solutions and Spiked Samplesmentioning
confidence: 99%